2011
DOI: 10.1158/0008-5472.can-11-0977
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprevention of Breast Cancer by Fish Oil in Preclinical Models: Trials and Tribulations

Abstract: Despite the perception that omega-3 fatty acids (n-3 FA) protect against breast cancer, epidemiologic studies have yielded inconsistent results. Although preclinical data have been, in general, more supportive of a protective effect of n-3 FA on breast cancer, inconsistencies still remain, which preclude definite conclusions or in-depth mechanistic investigations despite 30 years of research in this area. In this review, we discuss key variables that may account for inconsistencies of results across preclinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 25 publications
0
48
0
2
Order By: Relevance
“…Since breast cancer requires the coordinated activation of multiple cellular mechanisms, a multi-targeted approach is needed to prevent the development of mammary carcinogenesis. We have been interested in testing the combination of antiestrogens with n-3FA, an attractive class of compounds that could potentiate the beneficial effects of antiestrogens by inhibiting multiple cellular pathways potentially involved in mammary carcinogenesis (for review, see Signori et al 1 ). We believe that a major attractive feature of this approach is its safety since it allows us to combine a lower and hence less toxic dose of antiestrogens with n-3FA, compounds that are known to have inherent health benefits (that is, reduction in cardiovascular risk) beyond their potential chemopreventive benefit in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since breast cancer requires the coordinated activation of multiple cellular mechanisms, a multi-targeted approach is needed to prevent the development of mammary carcinogenesis. We have been interested in testing the combination of antiestrogens with n-3FA, an attractive class of compounds that could potentiate the beneficial effects of antiestrogens by inhibiting multiple cellular pathways potentially involved in mammary carcinogenesis (for review, see Signori et al 1 ). We believe that a major attractive feature of this approach is its safety since it allows us to combine a lower and hence less toxic dose of antiestrogens with n-3FA, compounds that are known to have inherent health benefits (that is, reduction in cardiovascular risk) beyond their potential chemopreventive benefit in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…1 While basic mechanisms are under investigation using preclinical models of mammary carcinogenesis, [2][3][4] we are testing concomitantly the clinical relevance of this approach in postmenopausal women using surrogate markers of breast cancer development (NCT00723398). While the primary end point of our clinical trial is a reduction in breast density, a wellestablished risk factor for breast cancer, 5 we are also examining the effects of the individual and combined administration of Ral and n-3FA on several biomarkers thought to be potentially involved in mammary carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…A review of 81 rodent studies concluded that dietary omega-6 fatty acids dose-dependently accelerate mammary tumorigenesis (11). Conversely, dietary EPA and DHA prevent mammary tumor development in animals (12)(13)(14)(15). The effect of omega-3 and omega-6 intake on breast cancer risk in humans has not been determined.…”
Section: Introductionmentioning
confidence: 99%
“…It has been postulated that the risk of breast cancer can be influenced by certain dietary components such as the amount and type of dietary fats ingested (3)(4)(5)(6)(7). Among the fatty acids, omega-3 (n-3) and omega-6 (n-6) fatty acids have been suggested to decrease and increase breast cancer risk, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Among the fatty acids, omega-3 (n-3) and omega-6 (n-6) fatty acids have been suggested to decrease and increase breast cancer risk, respectively. Despite the prevailing hypothesis that the ratio of n-3:n-6 may be important for chemoprevention, the optimum ratio has not been rigorously tested in many previously published reports (7). Furthermore, several chemoprevention studies in animal models used diets that were high in the percent of dietary calories provided from fat which are not consistent with the U.S. Dietary Guidelines (8).…”
Section: Introductionmentioning
confidence: 99%